2016
DOI: 10.18203/issn.2455-4510.intjresorthop20164834
|View full text |Cite
|
Sign up to set email alerts
|

Autologous grafting of non manupulated freshly isolated - adipose tissue derived stromal vascular fraction in single surgical sitting for treatment of knee osteoarthritis

Abstract: Background: Osteoarthritis (OA) is one of the major cause of morbidity, having a substantial influence on health quality of life, imposing enormous burden of cost on the health care system. It is a chronic degenerative disorder that is characterised by articular cartilage degeneration. It can be caused by aging, heredity and injury from trauma or disease. Primary symptoms of OA include joint pain, stiffness and limitation of movement. Disease progression is usually slow but can ultimately lead to joint failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Since ADSCs contain therapeutic properties ( i.e ., differentiation capability into a variety of cell lineage in vitro as well as having immunosuppressive, osteoinductive and anti-inflammatory features), they might be used for treatment of orthopedic major diseases such as degenerative OA[ 81 , 82 ].…”
Section: Orthopaedic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ADSCs contain therapeutic properties ( i.e ., differentiation capability into a variety of cell lineage in vitro as well as having immunosuppressive, osteoinductive and anti-inflammatory features), they might be used for treatment of orthopedic major diseases such as degenerative OA[ 81 , 82 ].…”
Section: Orthopaedic Disordersmentioning
confidence: 99%
“…Previous studies showed that administration of both ADSCs and SVF in early OA is a safe and therapeutically efficient approach[ 82 - 86 ].…”
Section: Orthopaedic Disordersmentioning
confidence: 99%
“…Besides, mechanically isolated autologous adipose tissue-derived stromal vascular fraction (SVF) origination from adipose tissue is optimal for treating KOA. Also, it might be a practical therapy option for those with degenerative OA [194].…”
Section: Adipose-derived Mesenchymal Stromal Cells (Adscs)mentioning
confidence: 99%
“…Lipoaspirate contains a large number of adipose-derived stem cells (ASCs). SVFs from fat tissue contain T cell regulators, endothelial precursor cells, preadipocytes, anti-inflammation macrophages, superoxide dismutase (SOD), IGF, TGF, FGF, hepatocyte growth factor (HGF), interleukin (IL), hematopoietic stem and progenitor cells, erythrocytes, fibroblasts, lymphocytes, monocyte/macrophages and pericytes are found in the SVF [ [10] , [11] , [12] , [13] ]. SVFs are known to promote burn healing by increasing cell proliferation and vascularization, enhancing inflammation, and increasing fibroblast activity [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%